The THE DEVELOPMENT OF PSYCHOSOCIAL CHARACTERISTICS IN JOHN STEINBECK’S “THE PEARL” - Aziiz Putrayuda; Thohiriyah (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study examines the characteristics of main characters of John Steinbeck's work "The Pearl" through the theory of Erik Erikson's psychosocial growth phases. It investigates how the characters navigate these stages against the backdrop of societal forces and personal goals. As the characters discover a precious pearl, their journey mirrors Erikson's stages, from trust to mistrust to integrity to despair. Each stage is characterized by conflicts and obstacles that develop characters’ personalities and interactions. This study uses qualitative analysis to explore the significant psychosocial processes represented in "The Pearl," resulting insights into psychosocial characters’ development and the complexity of their progress in a social context.